2020
DOI: 10.1590/fst.01619
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality parameters and chromatographic, spectroscopic, and thermogravimetric profile of Patauá oil (Oenocarpus bataua)

Abstract: The objective of this research was to evaluate the quality parameters and the chromatographic, thermogravimetric, and spectroscopic profile of Patauá oil (Oenocarpus bataua). All analyses were performed according to the Recommended Practices of the American Dil Chemists' Society (ADCS). The parameters obtained indicate conservation quality standards in accordance with Brazilian legislation. The fatty acid profile shows a predominance of ω-9, ω-6, and ω-3 fatty acids. The thermogravimetric behavior and differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
10
1
Order By: Relevance
“…Comparing the outcome of this investigation with that of Serra et al [24], who evaluated the quality standards of buriti (Mauritia flexuosa) oil and pracaxi (Pentachletra Macroloba) oil, high values of acidity and peroxide were found, a few above those determined in this investigation and recommended in the legislation (5.76mg KOH g -1 and 12.05mEq kg -1 ; 5.44mg KOH g-1 and 8.23mEq kg -1 , respectively). In another survey, Santos et al [25], when assessing the Patauá (Oenocarpus bataua) oil, found averages of 1.40mg KOH g -1 and 9.64mEq kg -1 in the acidity and peroxide index respectively, and Costa et al [6], in their investigations with Tucumã (Astrocaryum vulgare, Mart. ), found acid averages between 6.5mg to 20.3mg KOH g -1 and peroxides between 11.8 and 13.8mEq kg -1 [6].…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Comparing the outcome of this investigation with that of Serra et al [24], who evaluated the quality standards of buriti (Mauritia flexuosa) oil and pracaxi (Pentachletra Macroloba) oil, high values of acidity and peroxide were found, a few above those determined in this investigation and recommended in the legislation (5.76mg KOH g -1 and 12.05mEq kg -1 ; 5.44mg KOH g-1 and 8.23mEq kg -1 , respectively). In another survey, Santos et al [25], when assessing the Patauá (Oenocarpus bataua) oil, found averages of 1.40mg KOH g -1 and 9.64mEq kg -1 in the acidity and peroxide index respectively, and Costa et al [6], in their investigations with Tucumã (Astrocaryum vulgare, Mart. ), found acid averages between 6.5mg to 20.3mg KOH g -1 and peroxides between 11.8 and 13.8mEq kg -1 [6].…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 97%
“…Among the rates of polyunsaturated fatty acids, the largest ones are linoleic acid (ω-6) followed by linolenic acid (ω-3). In the investigation by Santos et al [25], with Amazonian fruits, 3 categories were listed, according to their ω-6 content. The first category for values below 4.9%; the second for values above 5%; and the third one for fruits with expressive rates of around 30.0%.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
“…These databases allow a reduction in testing and elaboration time, adjustment of parameters, savings in all aspects, as it occurs in different applications and design of industrial products, such as the production of edible oils, lubricants, biodiesel among others. These information bases can be expressed and ratified by the DSC curves (Santos et al, 2012(Santos et al, , 2019b.…”
Section: Thermal Analysis Of Pequi Pulp Oilmentioning
confidence: 99%
“…The great variety of Amazonian fruit species with high macro and micronutrients content potential makes this region a considerable source of food resources and of several additions of raw materials applicable to different industrial sectors. Among them, those with the highest energy rate derived from their lipid constitution, the oil seeds, stand out (Pereira et al, 2019;Santos et al, 2019aSantos et al, , 2019b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation